2018
DOI: 10.1186/s12889-018-6295-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic surveillance in a low resource setting: lessons from an evaluation of the Solomon Islands syndromic surveillance system, 2017

Abstract: BackgroundSolomon Islands is one of the least developed countries in the world. Recognising that timely detection of outbreaks is needed to enable early and effective response to disease outbreaks, the Solomon Islands government introduced a simple syndromic surveillance system in 2011. We conducted the first evaluation of the system and the first exploration of a national experience within the broader multi-country Pacific Syndromic Surveillance System to determine if it is meeting its objectives and to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…As a result of an increase in the amount of K, the probability of generation alarm on the first day of outbreaks decreased due to an increase in the level of alarm thresholds. The median, minimum and maximum timeliness (according to day) in Haar (k; 0.5) and db10 (k: 0.5) wavelets based method was 2 (1 to 14) and 2 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) respectively. This amount was less than the median timeliness of other algorithms.…”
Section: Timeliness Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of an increase in the amount of K, the probability of generation alarm on the first day of outbreaks decreased due to an increase in the level of alarm thresholds. The median, minimum and maximum timeliness (according to day) in Haar (k; 0.5) and db10 (k: 0.5) wavelets based method was 2 (1 to 14) and 2 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) respectively. This amount was less than the median timeliness of other algorithms.…”
Section: Timeliness Of Methodsmentioning
confidence: 99%
“…Due to many restrictions of the traditional surveillance system in early detection of the outbreak, the syndrome surveillance system is recommended to be used in such conditions. The syndrome surveillance includes collection, analysis, interpretation, and dissemination of health-related data defined in public health sectors (5)(6)(7). The objective of the syndrome surveillance system is to provide an early warning (system) for public health threats in near-real-time (8).…”
mentioning
confidence: 99%
“…1 ). The country’s population of 695,000 are dispersed over 992 islands and atolls; 78% reside in rural areas [ 27 ]. The pilot study was undertaken in Honiara, the capital of Solomon Islands.…”
Section: Methodsmentioning
confidence: 99%
“…In 2019, the Philippines reported outbreaks of dengue, diphtheria, measles, and polio (Wolfe et al, 2021). In the region, eight Japanese encephalitis cases were recorded in Nueva Vizcaya in 2017 (Gallardo et al, 2015), also in 2019, it was reported that a measles outbreak was declared in 4 of 5 provinces (Craig et al, 2018), and in August of the same year, dengue outbreak has been declared in 11 towns which prompted the local health officials to recommend that these areas be placed under a state of calamity (Smith, 2015). Emerging and re-emerging epidemics continue to pose tremendous threats to public health even with medical advances and the availability of vaccines.…”
Section: Introductionmentioning
confidence: 99%